Latin American business thinking in the 21st century (2019)
The objective of analyzing Latin American business thinking in this century is based on Camou, who believes that ideas have consequences and we can learn a lot about economic policy, society, and politics in general, from the analysis of what entrepreneurs think and how they communicate it in their political discourse. The ideas expressed in this discourse also allow us to infer the degree of influence in the definition of projects of a nation or region in a given historical moment. Another objective of this book, equally important, is to provide a basis for reflection and propose questions and lines of research that broaden the field of studies on Latin American business thinking. This book seeks to answer questions such as: how do Latin American businessmen, in the second decade of the 21st century, assume the different problems that touch them? What do they think about the different political, economic and social processes and how do they affect their productive work? and how do current events condition them politically and open up or close opportunities for economic enrichment or political representation? To do this, it includes a general definition of business thinking, as the set of ideas shared, in general terms (and with obvious exceptions), a group or community (entrepreneurs) that is characterized by conducting, coordinating or directing economic activities in entities independent (companies). This differs from the concept of ideology insofar as it includes a philosophical doctrine or a political program, which may or may not exist in business thinking. And it is also distinguished from “entrepreneurial” thinking because the latter’s goal is to develop a mentality that produces creative solutions to eliminate or reduce problems. In sum, a general definition is used to cover the varied Latin American literature on the subject.